A casebook on company law: Materials and commentary - KOH, Pearlie M. C. (Institutional Knowledge at Singapore Management University, 2021)
This volume is one of the first books to present a curated collection of cases that have forged the development of Company Law in Singapore. The book covers all the fundamental topics in Company Law, and each chapter is designed to guide the reader in the study of this rich area of law with the aid of suitably-placed commentary and thoughtful questions.